ANALISIS PENCIPTAAN LAPANGAN KERJA DI KOTA SEMARANG - Karningsih Karningsih (Serat Acitya, 2013)
Workforce development can be viewed from two aspects, namely supplies or labor supply and labor demand or requirement. Manpower development in Central Java province aimed at balancing between labor supply with labor demand. Employment issues in the city of Semarang is urgent to solve one of which is the high Unemployment rate. The purpose of this study to analyze the creation of jobs in the city, in order to reduce the number of unemployed. Sources of data obtained from primary data using interviews (in-depth interview) and Focused Group Discussion (FGD) and secondary data collected by the method of documentation. The research variables are supplies or labor supply (supply) and demand or labor requirements (demand). Engineering analysis using analysis of Strength, Weakness, Opportunity and Threat (SWOT). Results of this study indicate that the overall employment number is far fewer than the number of unemployed. As a result, the number of unemployed is difficult to bereduced (backlog). Job opportunities in the field of trade and services is quite open and evolving, but in terms of the availability of labor engaged in trade and services not in accordance with the needs. Employment strategy is to open opportunities as possible for investment is in any field. Job creation or business needs to pay attention to other aspects of the investment, industry, trade, cooperatives and SMEs, as well as the business needs to be raised so that the efforts to reduce the unemployment rate can be realized, and the longer the backlog of unemployed will decrease.